2014
DOI: 10.1186/1550-2783-11-2
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and ride time-to-exhaustion effects of an energy drink

Abstract: BackgroundCurrently, there are few studies on the cardiovascular and fatigue effects of commercially available energy drinks. This study investigated the effects of Monster energy drink (Monster Beverage Corporation, Corona, California), on resting heart rate (HR), heart rate variability (HRV), ride time-to-exhaustion, peak exercise HR, respiratory exchange ratio (RER), and peak rating of perceived exertion (RPE).MethodsThe study used a double-blind, randomized, placebo controlled, crossover design. After an 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 44 publications
(54 reference statements)
6
38
2
7
Order By: Relevance
“…In agreement with the findings of our study (19) on the predominantly myocardial effects of sugar-sweetened EDs are the following: 1) a report that the consumption of a sugarsweetened Monster ED (Monster Beverage; 2.0 mg caffeine/kg and 0.65 g sugar/kg) significantly elevated heart rate after 60 min compared with the placebo control (20), 2) a study in which blood pressure and heart rate responses to a sugarsweetened ED (Rockstar, Rockstar, Inc.; 240 mg caffeine and ;62 g sugar) resulted in significantly elevated blood pressure values (systolic blood pressure: +6.6 mm Hg; diastolic blood pressure: +4.2 mm Hg) compared with a sugarmatched placebo (21), and 3) findings from current studies evaluating the impact of sugar-free caffeinated energy shots [5-h Energy; 200 mg and 215 mg caffeine] on cardiovascular variables that showed that blood pressure variables significantly increased whereas heart rate did not change (22,23). Moreover, repeated intakes of an ED [8.3 oz of a Red Bull ED (Red Bull GmbH) 4 times over 24 h; 1 oz = 30 mL] increased blood pressure variables when compared with a water drink with equivalent amounts of caffeine (8 oz water with 80 mg caffeine) (24).…”
Section: Eds and Hemodynamics: Overall Effectssupporting
confidence: 81%
“…In agreement with the findings of our study (19) on the predominantly myocardial effects of sugar-sweetened EDs are the following: 1) a report that the consumption of a sugarsweetened Monster ED (Monster Beverage; 2.0 mg caffeine/kg and 0.65 g sugar/kg) significantly elevated heart rate after 60 min compared with the placebo control (20), 2) a study in which blood pressure and heart rate responses to a sugarsweetened ED (Rockstar, Rockstar, Inc.; 240 mg caffeine and ;62 g sugar) resulted in significantly elevated blood pressure values (systolic blood pressure: +6.6 mm Hg; diastolic blood pressure: +4.2 mm Hg) compared with a sugarmatched placebo (21), and 3) findings from current studies evaluating the impact of sugar-free caffeinated energy shots [5-h Energy; 200 mg and 215 mg caffeine] on cardiovascular variables that showed that blood pressure variables significantly increased whereas heart rate did not change (22,23). Moreover, repeated intakes of an ED [8.3 oz of a Red Bull ED (Red Bull GmbH) 4 times over 24 h; 1 oz = 30 mL] increased blood pressure variables when compared with a water drink with equivalent amounts of caffeine (8 oz water with 80 mg caffeine) (24).…”
Section: Eds and Hemodynamics: Overall Effectssupporting
confidence: 81%
“…It is worth noting that, even when using an energy drink containing ~2 times the concentration of caffeine, taurine and carbohydrate (160 mg, 2 g, and 57 g, respectively) when compared to those used in present study, also did not report an improvement in exercise endurance performance in trained male cyclists performing a 25-mile simulated race (Ivy et al;2009). The test used in the study (Cooper test), although recognized as an indirect endurance measurement field test, the time taken to perform the test is lower than those of studies reporting significant improvements in exercise performance, which were superior to 20 minutes (Campbell et al, 2013;Nelson & Dengel, 2014). When we refer to the influence of the energy drink on hemodynamic parameters, the literature is still contradictory in relation to outcome measures (Lovallo et al, 1991;Nelson & Dengel 2014;Wiklund et al, 2009) demonstrated that the consumption of 250 ml of Red Bull® in adults does not change heart rate.…”
Section: Discussioncontrasting
confidence: 64%
“…However, the results of these previous studies refer to rest or low-intensity exercise conditions (Nelson & Dengel, 2014;Lovallo et al;1991;Yamakoshi et al, 2013;Wiklund et al, 2009). To our knowledge, little is known about the influence of energy drinks on hemodynamic parameters during or immediately after physical activity, so our results are the first to analyze the influence of the energy drink on hemodynamic parameters in runners.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Subjective rating of exertion was also not changed. (52) A recent study (53) evaluated the acute effects of energy drinks on exercise performance in 19 professional female volleyball players. The players were recruited in a double blind, randomized, crossover study to determine grip strength, vertical jump and anaerobic power during three sessions.…”
Section: Renal Effectsmentioning
confidence: 99%